Types Of Social Conflicts In The Family And The Causes Of Their Own - Khoshimjanovna, Narzikulova Dilnoza (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article describes the causes, types of social conflicts in the family and ways to overcome them. The article deals with the main manifestations of family conflicts,as well as conflicts between spouses, conflicts between mother-in-law and daughter-in-law, conflicts between mother-in-law and son-in-law, conflicts between parents and children.The main directions of conflict resolution between parents and children are described.